The impact of feedback on the most important variables according to Elkinmetekih in the level of performance to pass the barrier for the beginner to the effectiveness of (110) meters hurdles - Faeq, Raed (Journal of Physical Education, 2011)
The Objective research to identify the most important variables associated with the performance of Alknymetekih pass the barrier to the effectiveness of (110) meters hurdles at beginners. As well as to identify the impact of feedback according to the most important variables in the level of performance Alknymetekih beginners (experimental group). The researcher used the experimental method. Research sample consisted of (12) students were tested from the second grade students in the Faculty of Physical Education - University of Babylon - for the academic year 2004 to 2005. Were selected by random draw in the manner as included on the curriculum (twelve) and the educational unit by two units each week in the educational zones per unit time (90) minutes. Attempts were recorded by junior runners Alfdaoah camera for the purpose of analysis of skill in a precise manner to study the variables Alkimnetekih where he managed a pointing-based study of the strengths and weaknesses affecting the skill. Program was used (Auto CAOR14) to extract the variables of research with respect to distances and angles. The time has been extracted through a special computer program called (Timer). The researcher used statistical methods appropriate for research. Conclude researcher emerged significant differences between the tests before and after the variable performance tests for a posteriori (the two sets of research). As well as the curriculum coupled with feedback Mapd performance based on motor according to the results of the analysis may have affected the performance improvement of the research sample (experimental group) in the post-test